6th Malaysian International Conference on Academic Strategies in English MY_CASELT2019 / Afni Anida Adnan - Adnan, Afni Anida (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2019)
The Universiti Teknologi Mara (UiTM) Negeri Sembilan team comprising Irma Ahmad, Mohamad Jafre Zainal Abidin, Mohd Nur Fitri Bin Mohd Salim and Afni Anida Adnan won the Dean’s Award at the 6TH Malaysian International Conference on Academic Strategies in English (My_CASELT2019) and 3rd LIID Exposition, which came with a RM1000 cash award. The UiTM Negeri Sembilan team outshone four other Top Gold Award winners with their poster entry titled “Benchmarking Undergraduates Listening Standards” in the My_CASELT’s poster presentation contest held on Aug 21.